AB0386 Relationship between extra-articular manifestations and joint surgery in rheumatoid arthritis. (12th June 2018) - Saidane, O.; Sellami, M.; Barhoumi, R.; Ben Tekaya, A.; Ajlani, H.; Tekaya, R.; Mahmoud, I.; Abdelmoula, L.
Abstract : Background: Extra-articular organ involvement is a serious condition in rheumatoid arthritis (RA) associated with increased mortality. These manifestations may affect the course of the disease, but could they accelerate the joint destruction and shorten the pre- joint surgical period? Objectives: Our objective was to study the impact of extra-articular manifestations (EAM) on joint surgery during RA management. Methods: It is a retrospective comparative study involving 500 RA patients (according to 1987 ACR or 2010 ACR/EULAR criteria) in rheumatology department between 2000 and 2014. The assessment of EAM was systematically done in RA diagnosis and during management. We compared 2 groups of RA patients according to the presence or not of EAM. Results: We enrolled 422 women and 78 men with mean age of 53.3 years (21–83) and mean disease duration of 12 years [2–40]. RA was Rheumatoid Factor positive and erosive in 71.4% and 90% cases respectively. A surgical procedure was considered necessary in 59 cases (11.8%). An EAM was diagnosed in more than a half of patients (62.4%) with a predominance of ocular and bone manifestation, mainly xerophthalmia (173 cases, 34.6%) and osteoporosis (120 cases, 24%). Secondary Sjögren's syndrome was confirmed in 70 cases. Pulmonary manifestations related to RA were noted in 70 patients (14%), especially diffuse interstitial pulmonary in 48 cases (9.6%). Renal involvement was present in 45 patients, of which interstitial renal disease was the most common manifestation (29 patients, 64.4%). Rheumatoid nodules (4.6%) and small vessel vasculitis (0.6%) were the most frequent skin manifestations. A significantly higher incidence of joint surgery was noted in osteoporotic RA patients (OR=1.91; p=0.029). There was no significant correlation between joint surgery resort and other EAM (table 1). Conclusions: Our study concluded to a higher incidence of EAM during RA management. Osteoporosis was the only EAM associated to greater frequency of joint surgery. Disclosure of Interest: None declared